Small Molecule Radiopharmaceuticals – A Review of Current Approaches - Chaturvedi, Shubhra; Mishra, Anil K. (Frontiers in Medicine, 2016)
Abstract Radiopharmaceuticals are an integral component of nuclear medicine and are widely applied in diagnostics and therapy. Though widely applied, the development of an “ideal” radiopharmaceutical can be challenging. Issues like specificity, selectivity, sensitivity and feasible chemistry challenge the design and synthesis of radiopharmaceuticals. Over time, strategies to address the issues have evolved by making use of new technological advances in the fields of biology and chemistry. This review presents the application of few advances in design and synthesis of radiopharmaceuticals. The topics covered are bivalent ligand approach and lipidizationas part of design modifications for enhanced selectivity and sensitivity and novel synthetic strategies for optimized chemistry and radiolabeling of radiopharmaceuticals.